Teaching activities for supporting students’ 4cs skills development in vocational education - Jalinus, Nizwardi; Sukardi, Sukardi; Wulansari, Rizky Ema; Heong, Yee Mei; Kiong, Tee Tze (Journal of Engineering Researcher and Lecturer, 2023)
The soft skills competencies needed in the industrial revolution 4.0 era on the 21st century are critical thinking, creativity, communication and collaboration or known as 4Cs Skills. This study aims at revealing a teaching activity that can develop and improve the 4Cs skills of vocational education students. This research was a quantitative study using a survey method. The research instrument used a questionnaire of the lecturers' statements about teaching activities carried out by educators to improve or develop the 4Cs skills of vocational education students. The respondents in this study were 403 educators that consisting of 200 educators from Universitas Negeri Padang (Indonesia) and 203 educators from Universiti Tun Hussein on Malaysia (Malaysia). Based on the research findings, it was found that the teaching activity that was most often carried out or appeared with a high percentage in improving students' 4Cs skills was problem solving to improve critical thinking skills, debate to improve communication skills, peer partner learning to improve collaboration skills and finally mind mapping to improve creative skills. Based on the results of this study, lecturers in the implementation of learning need to condition learning activities that can develop students' 4Cs skills, so that the competencies possessed are in accordance with the needs of the developing industry in this 21st century.